The Effect of Corporate Culture on Good Government Governance, Survey of Provincial, Regency and City Governments in the South Sumatra Region - Irlan Fery (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2019)
The purpose of this study is to determine the effect of Corporate Culture on Good Government Governance. The unit of analysis in this study is the regional government in South Sumatra, Palembang-Indonesia City. The results of the study show that the Corporate Culture has a significant effect on Good Government Governance which has characteristics possessed by someone to produce accurate information. Furthermore, it was found that corporate culture has implications for Good Government Governance.